Comparison of Growth of Campylobacteriaceae on Media Supplemented with Organic Acids and on Commercially Available Media - Jr., Arthur Hinton (International Journal of Poultry Science, 2006)
Experiments were conducted to compare the ability of a medium supplemented with organic acids to the ability of commercially available, non-selective media to support growth of Campylobacter spp. and Arcobacter butzleri. Liquid medium was composed of yeast extract-peptone basal broth (BB) that could be supplemented with an organic acid (OA) mixture of fumaric, lactic, malic, and succinic acids (BB + OA). Growth of cultures in BB and in BB + OA was compared to growth in Brucella broth, Mueller-Hinton broth, and Fluid Thioglycollate medium. Growth of A. butzleri and 10 of 15 Campylobacter isolates was significantly (P < 0.05) greater in BB + OA than in other broth media, while there was no significant difference in growth of the other 5 Campylobacter isolates in BB, BB + OA, Brucella broth, Mueller-Hinton broth, or Fluid Thioglycollate medium. Growth was also compared on agar media composed of BB + OA with Bacto agar and hemin (BA-hemin + OA) and on Remel® Blood Agar. Results indicated that there was no significant difference in the number of cfu`s recovered on BA-hemin + OA and on blood agar. Findings indicate that media supplemented with organic acids may be used as alternatives to some currently available commercial media for growing and maintaining Campylobacteriaceae.